(untitled) (Biological Sciences - PJSIR, 2005)
Pre-germinated cotton seedlings were grown under laboratory conditions to determine the affect of root and/or shoot impedance on their growth. The treatments studied were: (i) both shoot and root unimpeded, (ii) shoot impeded and root unimpeded, (iii) root impeded and shoot unimpeded, and (iv) both root and shoot impeded. Impeding the root alone, or root and shoot together, significantly (P < 0.05) reduced axial root length, total root length, and increased root diameter. The axial root length was reduced by 55%. The number of root laterals was not affected by impedance but lateral spacing was reduced significantly. Root diameter was increased in treatments where only roots had been impeded. Shoot diameter was significantly (P < 0.05) greater in the root and shoot impeded treatments. Shoot length was reduced by 15% when only the shoots were impeded, while 38% reduction was noted when both root and shoot were impeded. Shoot impedance did not cause any significant effect on the root growth rate when roots were unimpeded. In terms of shoot length, root impedance had no effect on shoot length, although the combined effect of root and shoot impedance was greater than shoot impedance alone.